Psikologis Pegawai Kantor - Puput Mulyono; Singgih Purnomo (Universitas Muhamadiyah Manado, 2022)
Democratic country has an obligation to ensure the fulfillment of its citizens’ rights, including access to quality public services. However, in Indonesia, the quality and effectiveness of public services currently face significant challenges, as evidenced by the decline in service standards. This study highlights the importance of psychological capital in improving job performance among public service employees, with job engagement as a mediating factor. Utilizing quantitative methods and convenient sampling, this study involved 317 participants. The variables were measured using the Individual Job Performance Questionnaire, Psychological Capital Questionnaire, and Utrecht Job Engagement Scale. The results showed that psychological capital predicts job performance, psychological capital predicts job engagement, and job engagement predicts job performance. In addition, this study showed that job engagement mediates the relationship between psychological capital and job performance. Therefore, increasing psychological capital and job engagement can improve the quality of public services, which has a positive impact on public trust and welfare.